Efficacy and Safety of Eravacycline in Obese Patients: A Post Hoc Analysis of Pooled Data From the IGNITE1 and IGNITE4 Clinical Trials. (13th November 2020) - Asempa, Tomefa E; Izmailyan, Sergey; Lawrence, Kenneth; Nicolau, David P
Abstract: Background: The increasing prevalence of obesity worldwide merits an examination of the efficacy and safety profiles of agents dosed by weight. Methods: Data for patients (n = 1037) were obtained from the pooled IGNITE1 and IGNITE4 randomized double-blind trials in which patients with complicated intra-abdominal infections received eravacycline 1 mg/kg (actual body weight [ABW]) every 12 hours or comparator (ertapenem 1 g every 24 hours or meropenem 1 g every 8 hours) intravenously. This post hoc analysis evaluated clinical cure rates, adverse events, and drug discontinuation rates stratified by body mass index (BMI) categories of BMI >40 kg/m 2 (Obese, Class III), BMI 35–39.9 kg/m 2 (Obese, Class II), BMI 30–34.9 kg/m 2 (Obese, Class I), BMI 25–29.9 kg/m 2 (Overweight), BMI 18.5–24.9 kg/m 2 (Healthy weight), and BMI <18.5 kg/m 2 (Underweight). Results: Clinical cure rates were high across BMI categories and ranged from 82% to 94% in the eravacycline group and 88.5%–100% in the comparator group. Similar cure rates were observed among eravacycline-treated healthy weight (126/134; 94%), overweight (127/146; 87%), and obese (BMI ≥30 kg/m 2 ; 110/129; 85.3%) patients. In the comparator group, a similar proportion of patients demonstrated clinical response (healthy weight [132/145; 91%], overweight [130/144; 90.3%], and obese [115/129; 89.1%]). Of the treatment-emergent adverse events that occurred in eravacycline-treated obese patients, a larger proportion were gastrointestinal-related (ie, nausea and vomiting); however, discontinuation rates were low and similar between eravacycline and carbapenems. Conclusions: This post hoc analysis demonstrates the therapeutic utility and acceptable safety profile of eravacycline dosed by ABW in obese patients (BMI ≥30 kg/m 2 ).